2012
DOI: 10.1371/annotation/71a6d947-c034-4749-a33d-971284ea3408
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Performance of the PointCare NOW System for CD4 Counting in HIV Patients Based on Five Independent Evaluations

Abstract: Introduction: Point-of-care (POC) CD4 testing can improve access to treatment by enabling decentralization and reducing patient loss-to-follow-up. As new POC CD4 technologies become available, their performance should be assessed before widespread deployment. This study reports the findings of five independent evaluations of the PointCare NOW CD4 system.Materials/Methods: Evaluations were conducted in Southern Africa (Mozambique, South Africa) and North America (Canada, USA). 492 blood samples (55 from HIV-neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…These parameters are routinely used in assessing treatment responses in resource-rich countries. HIVDR tests for patients on ART are not only important in monitoring individual patient treatment outcomes but also essential as public health tools in the routine assessment of the spread of drug-resistant variants at population levels (5,(17)(18)(19). Such data are vital in guiding a country's ARV drug regimen implementation strategy and in forecasting the need for new ARV drugs, especially in resource-limited settings where treatment options are limited (20)(21)(22).…”
mentioning
confidence: 99%
“…These parameters are routinely used in assessing treatment responses in resource-rich countries. HIVDR tests for patients on ART are not only important in monitoring individual patient treatment outcomes but also essential as public health tools in the routine assessment of the spread of drug-resistant variants at population levels (5,(17)(18)(19). Such data are vital in guiding a country's ARV drug regimen implementation strategy and in forecasting the need for new ARV drugs, especially in resource-limited settings where treatment options are limited (20)(21)(22).…”
mentioning
confidence: 99%
“…In the same report, the FDA-approved Cytospheres (CD4 Manual Count, Beckman Coulter, CA, USA) also repeat the same pattern with a high sensitivity yet low specificity, very low slope, and high absolute difference compared with the reference method at 99%, 32%, 0.58, and 58.6 cells/µL, respectively [39]. Conversely, a high positive bias leads to low sensitiity, typically illustrated by PointCare NOW (PointCare), also an FDA-approved platform [40], with a mean relative bias of 35% and a mean sensitivity of only 53% [41].…”
Section: Discussionmentioning
confidence: 59%
“…Because the ranges in the CD4 counts are wide, the mean bias is relative to the CD4 count, and should be reported as such. However, in our sample only two studies [29,30] reported the relative mean bias [27,30]. Future evaluations should report the relative mean bias, and more useful for comparison in future meta-analyses.…”
Section: Limitationsmentioning
confidence: 95%